NATIONAL EXPERIENCE IN THE DEVELOPMENT OF INFORMATION CONSUMPTION IN PUBLIC SERVICES: PROBLEMS AND SOLUTIONS - Yunusov, Mansur (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
This article highlights the national experience in the development of information consumption in public services: problems and solutions, increasing information literacy, problems and achievements of media education, media literacy culture of public servants in public civil service